Adaptive Equalization Using Artificial Neural Networks for a Visible Light Communication System - Alfaro-Marchant, M; Navarrete-Cardenas, R (Institute of Electrical and Electronics Engineers Inc., 2018)
The LEDs as lighting technology reaches a percentage higher than 90%. This work proposes an alternative use as communication technology. The assembly of a communications system using visible light (VLC) using a white light LED spotlight is presented. In communications, the equalizer that feeds the decisions, known as decision feedback equalizer (DFE), is used in many applications for the minimization of intersymbol interference (ISI) of the received signal. The aim is to test the artificial neural networks (ANN) for the training of a DFE equalizer, in a communication system by light source in indoor environment; seeking to minimize the Bit Error Rate (BER), in order to combat the adverse effects introduced by the channel and obtain greater transmission distances through VLC. © 2018 IEEE.